The differing impacts of operational and financial slack on occupational safety in varying market conditions - Wiengarten, Frank; Fan, Di; Lo, Chris K.Y.; Pagell, Mark (Journal of Operations Management, 2017)
AbstractOperations management scholars have long debated the right level of slack resources required to optimize a production system. Recent research suggests that the right level of operational slack, typically in the form of inventory, is very little but not none. However, this conclusion was reached without considering the role of slack resources in occupational safety, which is a critical oversight since the safety literature predicts that the reduction of operational slack harms workers. To address this gap, secondary data from 3945 publically listed U.S. firms is used to explore the role of operational and financial slack as well as market factors in occupational safety. The results show that decreasing operational slack harms workers and that this effect is mitigated when firms hold higher levels of financial slack. Furthermore, the external market environment also plays a crucial role in the operational slack – safety relationship.